Perception of Entrepreneurship Among Malaysian MBA Students - Abdullah, Nor Mawarniwati (2011)
Entrepreneurship has gained significant interest in the new era of globalization. In order to move towards a knowledge-based economy, Malaysia has identified entrepreneurship as one of the key elements to Malaysia has also begun to introduce various initiatives to stimulate entrepreneurial activity through various initiatives, promotions,trainings, funding and grants, with the aim to promote an effective ecosystems that encourage and support the creation of innovative new venture. Thus, this study attempts to explore the entrepreneurship perception among Malaysian MBA students. A Qualitative approach was used to investigate this topic. Five themes have emerged from the analysis of the data from the 14 respondents, which are: idea generation, relational skill, satisfaction of growing own business, risk of failure and entrepreneurship programs. The study describes an overall view of how the Malaysian MBA students perceive entrepreneurship from the birth of entrepreneur, skills required to be successful, what drives the entrepreneur, the worst aspect of being entrepreneur and government‟s initiatives to support entrepreneurs.